Heterostructured SmCoO₃/rGO composite for high-energy hybrid supercapacitors - Isacfranklin, M. (2021)
A supercapacitor is an efficient energy storage system that acts as an excellent booster to deliver high power density required for batteries and fuel cells. Recently, composite material–based supercapacitors have attracted much more interest as promising greener and more capable candidates in energy-saving use. In this work, samarium cobalt oxide–decorated reduced graphene oxide (SmCoO₃/rGO) was prepared employing solvothermal route and used as reliable electrode material. The maximum specific capacity achieved was 30.80 mAh/g for 1 A/g of SmCoO₃/rGO nanocomposite with capacity retention of 86.95%@5A/g over 5000 charge discharge cycles. Better electrochemical performance of samarium and reduced graphene oxide nanostructures prevent the transfer of electrons through electrochemical active sites, creating electronic and structural diversity of electro active material. In addition, SmCoO₃/rGO/AC hybrid supercapacitor device that delivered good energy and power density of 52 W h/kg and 752 W/kg at 1 A/g was designed. 74.28% capacitive retention and 98.26% coulombic efficiency was maintained over 15,000 cycles.